النموذج المثالي للبيروقراطية عندماكس فيبر في ميزان التحليل الإستراتيجي لـميشال كروزييه - بالنور,يوسف (University of Eloued جامعة الوادي, 2024)
ملخص: أرتكزت تحاليل "كروزييه" في مستهل دراساته على علم الإجتماع العام، وهذا لتوسيع نطاق نظرية في تحليل التنظيمات التي قدمت إسهامات حاسمة في بناء تفكير جديد، ثم قام بمساهمة جادة في دراسة الظاهرة البيروقراطية، والتي أنطلق منها في تحليله ليصل إلى النسق الإجتماعي ككل محاولا وضع تحليل جديد لنظرية البيروقراطية، من خلال صياغة ما عرف عنه بـ: "التحليل الإستراتيجي للمنظمات"، وذلك من خلال فهم أكبر لكيفيات بناء الأفعال لأعضاء التنظيم ومعاينة سلوكهم – رؤساء ومرؤوسين، بحيث مكنت "كروزييه" من دراسة وضعيات تتميز بعلاقات السلطة في ظل التناقضات النسقية، وهذه التناقضات ستؤدي إلى إخلال التوازن الداخلي لنسق علاقات السلطة داخل التنظيم، ومن ثم ظهور شبكات ضاغطة وممارسة من طرف كل الفاعلين في التنظيم لتعبر كلها بما أسماه عن العقلانية المحدودة التي تؤكد أن لكل فاعل أفقا محدودا ونسبيا بينه وبين الفاعلين الآخرين، وكان يهدف "كروزييه" بتحليله الإستراتيجي إلى تطوير مقاربة في أنماط الصيرورات التنظيمية المبنية على السلطة وعلاقاتها وتفاعلاتها بين الفاعلين. في هذا الإطار قدم "كروزييه" إنتقادات لكل من النظريات الكلاسيكية ولمدرسة العلاقات الإنسانية اللذان يكتفيان التوصيف المسبق وإعطاء أعضاء التنظيم أدوارا محددة وسلوكات عقلانية متوقعة، لذا يرى "كروزييه" أن الإنسان في التنظيم لا يمكن إعتباره كيَد عاملة كما تصورته نظرية الإدارة العلمية، ولا كيَد وقلب حسبما تصورته مدرسة العلاقات الإنسانية، فكلها بحسبه تغفل فكرة أن الإنسان يملك عقلا يفكر به وله حرية فيما يتصرف فيه، ولذا أقترح "كروزييه" بدلا من ذلك نظرية العقلانية المحدودة، حيث يتمتع فيها كل فاعل بعقلانية محددة تسمح له بتدبير إستراتيجية خاصة به، يحاول من خلالها إيجاد التدابير اللازمة لقضاء حوائجه وتحقيق مآربه، وهذا يعنى أن الفرد في التنظيم عبارة عن فاعل مستقل قادر على الحساب والتحكم والتسيير، وقادر على التأقلم والإبتكار في ظل الظروف السائدة. Abstract : At the beginning of his studies, Crozier's analyzes were based on general sociology, in order to expand the scope of a theory in analyzing organizations that made decisive contributions to building new thinking. Then he made a serious contribution to the study of the bureaucratic phenomenon, from which he proceeded in his analysis to reach the social system as a whole, trying to establish A new analysis of the theory of bureaucracy, through the formulation of what is known as: “strategic analysis of organizations,” through a greater understanding of how to build actions for organizational members and observe their behavior - superiors and subordinates, this enabled Crozier to study situations characterized by power relations in light of systemic contradictions, and these contradictions would lead to an disruption of the internal balance of the system of power relations within the organization, and then the emergence of pressure networks and practice by all actors in the organization, all of which express what he called the limited rationality that confirms Every actor has a limited and relative horizon between him and other actors, and Crozier aimed, with his strategic analysis, to develop an approach to the patterns of organizational processes based on power and its relationships and interactions between the actors. In this context, Crozier presented criticisms of both classical theories and the school of human relations, which content themselves with prior descriptions and giving members of the organization specific roles and expected rational behaviors. Therefore, Crozier believes that the human being in the organization cannot be considered a working hand as envisioned by scientific management theory, nor a hand. And the heart, as conceived by the school of human relations, all of them, according to him, ignore the idea that a person has a mind to think with and has freedom in what he acts in it, and therefore Crozier proposed instead the theory of limited rationality, where each actor has a specific rationality that allows him to plan his own strategy, through which he tries to find the necessary measures to meet his needs and achieve his goals. This means that the individual in the organization is an independent actor capable of calculation, control and management, and is able to adapt and innovate under the prevailing circumstances.
Keywords: البيروقراطية; التحليل الإستراتيجي